2021
DOI: 10.1021/jacs.0c11336
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects of Photopharmacology: Insight into the Binding of Photoswitchable and Photocaged Inhibitors to the Glutamate Transporter Homologue

Abstract: Photopharmacology addresses the challenge of drug selectivity and side effects through creation of photoresponsive molecules activated with light with high spatiotemporal precision. This is achieved through incorporation of molecular photoswitches and photocages into the pharmacophore. However, the structural basis for the light-induced modulation of inhibitory potency in general is still missing, which poses a major design challenge for this emerging field of research. Here we solved crystal structures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 71 publications
0
20
0
1
Order By: Relevance
“…Recent advancements in membrane protein structural biology, in particular cryo-EM, have substantially increased the number of available ion channel and receptor structures [ 128 , 129 ] that can be used as input to design photoswitchable ligands. In this regard, a recent study has reported crystal structures of the glutamate transporter homologue Glt Tk in complex with a photoswitchable inhibitor in either cis or trans form [ 129 ]. In addition, these new experimental structures have broadened the range of templates available to build homology models for other ion channels without experimental structures.…”
Section: Conclusion and Perspectivesmentioning
confidence: 99%
“…Recent advancements in membrane protein structural biology, in particular cryo-EM, have substantially increased the number of available ion channel and receptor structures [ 128 , 129 ] that can be used as input to design photoswitchable ligands. In this regard, a recent study has reported crystal structures of the glutamate transporter homologue Glt Tk in complex with a photoswitchable inhibitor in either cis or trans form [ 129 ]. In addition, these new experimental structures have broadened the range of templates available to build homology models for other ion channels without experimental structures.…”
Section: Conclusion and Perspectivesmentioning
confidence: 99%
“…Examples of important L-aspartate derivatives include biodegradable metal chelators, metallobeta-lactamase and glutamate transporter inhibitors, photoswitchable and photocaged drug-like molecules, as well as various N-heterocycles and other chiral synthons that are widely used in pharmaceutical synthesis. [19][20][21] We have recently initiated structure-based and computer-aided protein engineering studies with the aim to enlarge the electrophile substrate scope of EDDS lyase to further increase its synthetic usefulness.…”
Section: Communicationmentioning
confidence: 99%
“…For the first time, there is a single nanosystem that enables sustained 1 O 2 generation and sufficient oxygen supply during the fPDT process by alternatively applying PDT and PTT regulated by two NIR laser beams. Dual-light irradiation can provide more controllability and has recently been widely used in multiple biological and biomedical fields, such as cancer treatment, [21] antibacterial, [40] photopharmacology, [41] optogenetics, [42] and optical-control of protein function and signaling, [43][44][45] etc. Moreover, the replacement of the dark cycle of conventional fPDT with PTT further enhanced the overall outcome of the anticancer phototherapy due to the synergistic effect of PDT and PTT (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%